2010
DOI: 10.3899/jrheum.100542
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Cellular Immune Response to Outer Membrane Protein ofSalmonella typhimuriumin Patients with Enthesitis-related Arthritis Subtype of Juvenile Idiopathic Arthritis

Abstract: in JIA-ERA, OMP is the major antigenic target recognized by both SFMC and PBMC. Response to OMP is independent of specific bacterial response, suggesting that OMP is the immunodominant antigen. In these patients, absence of significant humoral response suggests response to OMP is mainly T cell mediated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 26 publications
2
9
0
1
Order By: Relevance
“…Among these 12 patients, 11 showed a proliferative response to OMP. These outer membrane proteins are accessible to the immune system and might represent a T cell-mediated target of synovial fluid and peripheral blood mononuclear cells in patients with enthesitisrelated arthritis [54].…”
Section: The Potential Role Of Bacteria In Juvenile Idiopathic Arthritismentioning
confidence: 99%
“…Among these 12 patients, 11 showed a proliferative response to OMP. These outer membrane proteins are accessible to the immune system and might represent a T cell-mediated target of synovial fluid and peripheral blood mononuclear cells in patients with enthesitisrelated arthritis [54].…”
Section: The Potential Role Of Bacteria In Juvenile Idiopathic Arthritismentioning
confidence: 99%
“…Stoll et al demonstrated that in children with ERA [ 8 ], serum IgA against B. fragilis was directly proportional to fecal Bacteroides abundance, while controls had the opposite relationship, which they took to indicate that patients had a more pathogenic response against this organism. Additionally, Singh et al (2011) demonstrated increased T cell responses to the Salmonella outer membrane protein in ERA patients compared to controls [ 54 ].…”
Section: Mechanisms By Which the Microbiota Might Predispose To Jiamentioning
confidence: 99%
“…Despite these differences, serum IgA and IgG antibody against F. prausnitzii and B. fragilis were similar between controls and patients. There is also some evidence of a cellular immune response to the outer membrane protein of Salmonella typhimurium in juvenile SpA patients compared to healthy controls [54]. Intriguingly, study of the microbiota of juvenile SpA patients revealed that patients could be stratified into two distinct clusters, one dominated by Bacteroides genus members, the other by Akkermansia muciniphila.…”
Section: Juvenile Spamentioning
confidence: 99%